3D Printed composite for simulating thermal and mechanical responses of the cortical bone in orthopaedic surgery. (November 2018) - Tai, Bruce L.; Kao, Yi-Tang; Payne, Nolan; Zheng, Yihao; Chen, Lei; Shih, Albert J.
Highlights: A 3D printable composite, 3DPIC, is introduced for mimicking the cortical bone in surgery. 3DPIC has a tunable elastic modulus and strength based on the composition. 3DPIC has a comparable modulus to the cortical bone but a much lower strength. 3DPIC has similar force and temperature responses to the cortical bone in drilling. Abstract: Synthetic bones made of polyurethane (PU) foams or glass-fiber reinforced epoxy are often used in surgical training, planning, and tool analysis, but these materials cannot be 3D printed for a patient-specific design. This paper introduces a new type of bone-mimicking material made by the binder jetting technology and a post-strengthening process with epoxy, namely 3D polymer-infiltrated composite (3DPIC). 3DPIC has been previously evaluated by surgeons as a proper alternative to commercial synthetic bones, but no quantitative testing data is available. Therefore, a series of experiments are conducted in this study to verify the use of 3DPIC. The first part of experiments includes the measurement of mechanical properties using the four-point bending and the measurement of thermal properties. The second part of experiments is to test drilling haptic and thermal responses of 3DPIC as compared to the cortical bone. The results show that 3DPIC has a comparable elastic modulus but a lower strength than the cortical bone. 3DPIC can produce realistic drilling force and torque as well as representative temperature change in drilling operations, but the bone debris tends to be more ductile and continuous than that of the cortical bone. Applications and limitations of 3DPIC are discussed based on these results.